Analysis of health investment decisions: the moderating effects of health values and perceived environmental uncertainty - Lailiyah, Kusroh; saraya, sitta; Abdullah, Lukman Zaini; Apriliyanto, Nanang (Institute of Computer Science (IOCS), 2025)
The COVID-19 pandemic has officially ended, yet many individuals continue to struggle with achieving health independence. This is evident from the ongoing complaints regarding the inability to pay monthly contributions to the National Health Insurance (JKN), despite an overall increase in JKN enrollment compared to the pre-pandemic period. One of the main barriers to health independence appears to be the lack of public understanding regarding health investment, which is the core issue and central focus of this study. This condition may be influenced by various financial factors, particularly in terms of financial attitude and financial knowledge. This study aims to analyze the influence of financial attitude and financial knowledge on health investment decisions, with health value and perceived environmental uncertainty serving as moderating variables. A quantitative approach was employed, with primary data collected from 200 respondents who decided to invest in their health after experiencing serious health issues during the COVID-19 pandemic. The data were analyzed using SmartPLS. The findings reveal that financial attitude plays a significant role in encouraging individuals to make health investment decisions. This effect becomes stronger and more positive in situations of high environmental uncertainty. However, when viewed through the lens of strong personal health values, this relationship turns significantly negative. Conversely, although financial knowledge has the potential to support health investment decisions, its influence is not consistently evident. When moderated by health value and perceived environmental uncertainty, financial knowledge does not appear to have a significant impact on health investment decisions. Increasing JKN participation requires a combination of developing positive financial attitudes, improving financial literacy, strengthening public trust, and aligning communications with public health values ??and priorities.